(3GdMhceI GdeDSSjI h GdCOGA GdeGdj GdGSJQGJjLj ddeUGQa (B/s - (3WGdH, YdGA aQMGfs; (3GdeTgOGfj, GjeGf TjMGf s ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2011)
(3GdebOeI(B-(3GdaUd GdChd (B: (3OQGSGJ aj GdMhceI GdeDSSjI hGdCOGA GdeGdj(B-(3GdaUd GdKGfj (B: (3GdMhceI GdeDSSjI (B: (3GdeHMK GdChd (B: (3eaghe GdMhceI GdeDSSjI , GdfTCI hGdJWhQ GdJGQjNj , GdCgejI (B: (3GdeHMK GdKGfj (B: (3eHGOF GdMhceI GdeDSSjI (B: (3GdCgOGa , GdeMOOGJ (B: (3GdeHMK GdKGdK (B: (3OhQ GdMhceI GdeDSSjI aj GdeUGQa hGdJMOjGJ GdJj JhGLggG(B-(3GdaUd GdKGdK (B: (3GdCOGA GdeGdj GdGSJQGJjLj (B: (3GdeHMK GdChd (B: (3eaghe GdCOGA GdeGdj hGdJMdjd GdeGdj (B: (3GdeHMK GdKGfj (B: (3Jbjje GdCOGA hGdeDTQGJ GdeGdj(B-(3GdaUd GdQGHY (B: (3MGdI OQGSjI (B: (3GdeHMK GdChd (B: (3hUa eJZjQGJ GdOQGSI hJTNjUgG (B: (3GdeHMK GdKGfj (B: (3GdJMdjd GdEMUGFj dJHGjf JHfj eJZjQGJ GdOQGSI (B: (3GdeHMK GdKGdK (B: (3bjGS YdGbGJ GdGQJHGW Hjf eJZjQGJ GdOQGSI (B: (3GdeHMK GdQGHY (B: (3JMdjd hGNJHGQ CKQ GdMhceI GdeDSSjI aj GdCOGA GdeGdj GdGSJQGJjLjs
(3GdedGMb U(B.169 (3HHdjhZQGajG(B: (3U(B.177- 199s
Keywords: (3EOGQI GdCYeGds; (3GdCOGA GdeDSSjs; (3GdHfhcs; (3GdbWGY GdYGes